Inspiratory muscle training improves heart rate variability and respiratory muscle strength in obese young adults. - Piangkwan Sa-Nguanmoo; Sainatee Pratanaphon; Arisa Parameyong; Jitapa Chawawisuttikool; Krekwit Shinlapawittayatorn; Nipon Chattipakorn; Siriporn C Chattipakorn (PLoS ONE)
This study determined the effect of inspiratory muscle training (IMT), a non-pharmacological treatment on pulmonary function, inspiratory muscle strength and autonomic modulation measured by heart rate variability in obese young adults. The study hypothesized that IMT improves inspiratory muscle strength and enhances autonomic modulation in obese young adults. Nineteen obese young adults (body mass index (BMI) ≥ 25 kg/m², according to the Asian-Pacific cutoff points), aged 18-25 years, were assigned to either a control group (n = 9) or an inspiratory muscle training (IMT) group (n = 10). The IMT group underwent a training load of 55% of maximum inspiratory pressure (MIP) and the control group had no load. Both groups performed 30 breaths twice a day, 5 days/week for 4 weeks. IMT load was readjusted weekly. Pulmonary function, inspiratory muscle strength and heart rate variability (HRV) were measured at baseline, and weeks 2 and 4. By week 2, inspiratory muscle strength was significantly improved in the IMT group (p < 0.05). The low-frequency/high-frequency (LF/HF) ratio was also reduced, suggesting improved sympathovagal balance. These changes indicate potential cardiovascular benefits of IMT in this population. However, no differences in pulmonary function or inspiratory muscle endurance were found between the groups. These findings suggested that IMT improves heart rate variability and increases inspiratory muscle strength in obese young adults.